Neighborhood Deprivation Index and Postpartum Depression: Association Varies by Race and Ethnicity [A244]. (May 2022) - Onyewuenyi, Ticara L.; Peterman, Kelli; Tutwiler, Ameisha; Weintraub, Miranda Ritterman; Pettway, Bria L.; Avalos, Lyndsay A.
Abstract : INTRODUCTION: Little research has evaluated the influence of neighborhood deprivation index (NDI) on postpartum depression (PPD). This study evaluated the effects of NDI and race/ethnicity independently and jointly. METHODS: This is a retrospective cohort study of Kaiser Permanente Northern California members aged >15 years who delivered a live-born infant between October 7, 2012, and May 31, 2017. PPD was identified using depression diagnoses obtained the day after delivery through 12 months postpartum. NDI was categorized into quartiles; the top quartile represented the highest deprivation. Multivariable logistic regression was conducted to assess the association between NDI and PPD. We performed analyses stratified by race/ethnicity to assess for effect modification. RESULTS: Among 177, 511 live births, 122, 995 were to unique mothers; among those, 18, 510 (12.5%) had PPD. PPD ranged from 20.8% in the lowest NDI quartile to 27.8% in the highest. Higher NDI was associated with greater odds of PPD (Q4, referent Q1: adjusted odds ratio [aOR], 1.16; 95% CI, 1.10–1.23). Associations between NDI and PPD varied by race/ethnicity. NDI was not associated with PPD among Hispanic women. Black women had the highest odds of PPD for all NDI quartiles (Q2: aOR, 1.50, 95% CI, 1.17–1.91; Q3: aOR, 1.64, 95% CI, 1.30–2.07; Q4: aOR, 1.78, 95% CI, 1.42–2.22; referent for all comparisons Q1). CONCLUSION: There were significant variations in PPD rates according to race and ethnicity that persisted regardless of NDI. Findings from this study suggest that while geographic targeting of mental health services may be informative, the role of systemic racism should be considered.